(untitled) (International Seven Journal of Multidisciplinary, 2024)
Snacks are practical, quick-to-eat foods that are often included in snacks and small meals and have a major influence on the general population’s diet. However, they are not recognized as healthy foods due to their low nutritional properties, excess fat, high calorie content and because they exclude people with celiac disease. This highlights the need to develop projects aimed at producing snacks with superior sensory and palatable characteristics. To meet this demand, a product was developed with the addition of chickpeas, carrots and oat flour, replacing the wheat flour commonly used in existing formulations. This was developed by making a vegetable paste and molding a dough compatible with the typical shapes of these foods. The results of the water activity, humidity and pH analyses showed levels very close to those of snacks sold on supermarket shelves, but the concentration of protein in the product was a major highlight (over 20%), demonstrating that a tasty, convenient product with a long shelf life can have high nutritional values. In the sensory analysis, the product stood out in terms of crunchiness, with the sum of the concepts “I loved it” and “I liked it” being 89.8%, and taste with 87.7%.